Bauhaus syncopated – jazz and dance movement in the work of Piet Mondrian - Jóźwiak, Karol (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
In this chapter we point at a peculiar junction between different phenomena of the early twentieth century. We survey new ideas around the Bauhaus school with a particular focus on performance and dance, the work of Piet Mondrian and his interest in music and dance, as well as the culture of jazz. This historical and the-oretical context is further developed in art-based research aiming at interpreting the work of Piet Mondrian in the form of dance. Co-author of this chapter au-thored a performative lecture in Muzeum Sztuki and a diploma spectacle at the Academy of Music in Łódź (both in 2019). This performative experience is used as a mode of further developing the research on the discussed junction, as well as a kind of pointe to our chapter (visual essay consisting of the documentation of both events).